(untitled) (Journal of Social Sciences Review, 2023)
In the developing world, a substantial revenue (0.7 billion per annum in Pakistan (Resources & Tel, 2018) while in India 0.6 billion is lost due to WBDs per year (Pathak, 2015) is spent, by citizens as well as the state, on the treatment of avoidable Water Borne Diseases (WBD), which is often far greater than the investment required to improve water quality. Many agencies like Public Health Engineering, WASA, PCSIR, PCRWR etc. are carrying out water quality tests regularly and publish their findings periodically. However, none of these studies, so far, have included the disease incidence, direct and indirect costs borne by the citizens as well as the state, due to poor water quality and poor hygiene practices such as environmental hygiene, personal hygiene, water and food hygiene. From the result analysis of E.Coli, Total Fecal Coliform Bacteria (TFCB) and Total Plate Count (TPC) Tests it was found that only 5.13 % of samples of water were contaminated with E.Coli and TFCB but from the surveys it was concluded that the disease incidence is more in the study area